The ethical intelligence: a tool guidance in the process of the negotiation - Cristina Seijo; Gilma Romaña (Universidad del Magdalena, 2014)
The present article is the result of a research, which has as object present a theoretical contrast that invites to the reflection on the ethical intelligence as a tool guidance in the negotiation. In the same one there are approached the different types of ethical intelligence; spatial intelligence, rational intelligence, emotional intelligence among others, equally one refers associative intelligence to the processes of negotiation and to the tactics of negotiation. In this respect, it is possible to deal to the ethical intelligence as the aptitude to examine the moral standards of the individual and of the society to decide between what this one correct or incorrect and to be able like that to solve the different problematic ones for which an individual or a society cross. For this reason, one invites to start mechanisms of transparency and participation by virtue of which the ethical intelligence is born in mind as the threshold that orientates this process of negotiation.